Unauthorised receipt or acceptance of gratification and conflict of interest in the workplace - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Eishan Jan, Mohammad Naqib (The Malaysian Current Law Journal Sdn Bhd, 2016)
In the discharge of his duties and functions, an employee is expected to act with complete honesty and integrity no matter what position the employee may hold in an organisation. He should not betray the trust and confidence reposed on him and this would include theft, criminal misappropriation, criminal breach of trust, fraud, forgery and cheating, among others.1 Once an employee exhibits dishonesty or a lack of integrity, the trust and confidence reposed in him by the employer can no longer subsist. Furthermore, an employee must avoid situations in which his personal interests could conflict or might be seen to be in conflict with the interests of the company. This includes receiving or accepting for his own benefit any gratuity, emolument, or payment of any kind from any person having or intending to have any business with the employer. Accepting or receiving bribery or corruption from individuals such as the personnel of companies with which the company does business is a serious criminal offence and can cause significant reputational damage of the company. In light of the above, this paper discusses the issue of unauthorised receipt or acceptance of gratification and conflict of interest in the workplace.